1989
DOI: 10.1073/pnas.86.12.4569
|View full text |Cite
|
Sign up to set email alerts
|

Archaebacterial DNA-dependent RNA polymerases testify to the evolution of the eukaryotic nuclear genome.

Abstract: Genes for DNA-dependent RNA polymerase components B, A, and C from the archaebacterium Sulfolobus acidocaldarius and for components B", B', A, and C from the archaebacterium Halobacterium halobium were cloned and sequenced. They are organized in gene clusters in the order above, which corresponds to the order of the homologous rpoB and IpoC genes in the corresponding operon of the Escherichia coli genome. Derived amino acid sequences of archaebacterial components A and C were aligned with each other and with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
120
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(128 citation statements)
references
References 44 publications
7
120
1
Order By: Relevance
“…64). The archaeal and eukaryal polymerases are closely related in subunit complexity and sequence (65,66). Fourteen RNA polymerase subunits are encoded by 8 loci: rpoDN (Sso0071, 5140), rpoHB-ЈBЈЈAAЈЈ(Sso5468, 0227, 3254, 0225, 0223), rpoG (Sso0277; ortholog of S. acidocaldarius RpoG) (67), rpoL (Sso5577), rpoEЈEЈЈ (Sso0415, 5798), rpoF (Sso0751; ortholog of M. thermoautotrophicum rpoF) (68), rpoK (Sso6768) and rpoP (Sso5865; ortholog of M. thermoautotrophicum rpoP) (68).…”
Section: Transcriptionmentioning
confidence: 99%
“…64). The archaeal and eukaryal polymerases are closely related in subunit complexity and sequence (65,66). Fourteen RNA polymerase subunits are encoded by 8 loci: rpoDN (Sso0071, 5140), rpoHB-ЈBЈЈAAЈЈ(Sso5468, 0227, 3254, 0225, 0223), rpoG (Sso0277; ortholog of S. acidocaldarius RpoG) (67), rpoL (Sso5577), rpoEЈEЈЈ (Sso0415, 5798), rpoF (Sso0751; ortholog of M. thermoautotrophicum rpoF) (68), rpoK (Sso6768) and rpoP (Sso5865; ortholog of M. thermoautotrophicum rpoP) (68).…”
Section: Transcriptionmentioning
confidence: 99%
“…The largest of these subunits contains eight highly conserved domains, designated regions A through H (2), which are common to all prokaryotic and eukaryotic homologues (3). Unlike all other members of this protein family, however, the largest subunit of eukaryotic RNA pol II has an additional C-terminal domain (CTD), comprising a varied number of tandemly repeated heptapeptides with the consensus sequence Tyr-1-Ser-2-Pro-3-Thr-4 -Ser-5-Pro-6 -Ser-7 (4).…”
mentioning
confidence: 99%
“…Evidence from sequence similarity studies between RNA polymerases suggests that archaeal transcription shared certain components with that of the Eukarya (Puhler et al 1989), a conclusion further supported by the discovery of TFIIB in Pyrococcus furiosus (Ouzounis and Sander 1992) and TBP in P. woesei (Rowlands et al 1994). The strong similarity of archaeal transcription initiation factors with their eukaryotic counterparts has reinforced the concept that these domains shared an ancestral transcriptional apparatus.…”
Section: Introductionmentioning
confidence: 59%
“…Furthermore, these analyses may reveal how archaea respond to environmental challenges, in particular, given their possible association with various aspects of human disease (Eckburg et al 2003). Several previous studies have shown that the RNA polymerase core enzyme exhibits structural similarity between the Archaea and the Eukaryota (Puhler et al 1989). Moreover, the minimal set of factors required for in vitro transcription initiation in archaea consists of TATA-box binding protein (TBP), TFIIB and RNA polymerase II (Werner and Weinzierl 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation